Exploring Genetic Variability, Correlation and Path Analysis in Fenugreek (Trigonella foenum-graecum L.) for Crop Improvement - Shivraj; Kumar, Pramod; Kumar, Rajneesh; Chouhan, Shambhu; Tutlani, Aman (International Journal of Bio-resource and Stress Management, 2023)
The present investigation has been carried out at Agricultural Research Station, Mandor, Jodhpur during month of Rabi season (October, 2016–April, 2017) to evaluate 35 genotypes of fenugreek to assess extent of genetic variability, heritability, genetic advance with correlation and path coefficient for yield and its contributing characters. The material was planted in Randomized Block Design with three replications and observations were recorded on individual plant basis. Analysis of variance recorded significant between genotypes for the characters studies. The genotypic and phenotypic coefficient of variation was higher for seed yield per plant (g). High heritability (broad sense) coupled with high genetic advance as percentage of mean was observed for branches per plant, no. of pods per plant, pod length (cm), seeds per pod, test weight (g) and seed yield per plant (g). The correlation analysis at genotypic and phenotypic level, seed yield per plant was positively significant correlated with branches per plant, number of pods per plant, test weight, harvest index, days to 50% flowering, pod length and seeds per pod, but except days to maturity at phenotype level which was correlated with negative significance. Path coefficient analysis suggested that the highest positive direct effect on grain yield per plant was exerted by harvest index (%) followed by seeds per pod, test weight, days to 50% flowering, plant height and branches per plant. Number of pods per plant, pod length (cm) and days to maturity contributed considerable negative direct effect on grain yield per plant.